Augmenting distractor filtering via transcranial magnetic stimulation of the lateral occipital cortex. (November 2016) - Eštočinová, Jana; Lo Gerfo, Emanuele; Della Libera, Chiara; Chelazzi, Leonardo; Santandrea, Elisa
Abstract: Visual selective attention (VSA) optimizes perception and behavioral control by enabling efficient selection of relevant information and filtering of distractors. While focusing resources on task-relevant information helps counteract distraction, dedicated filtering mechanisms have recently been demonstrated, allowing neural systems to implement suitable policies for the suppression of potential interference. Limited evidence is presently available concerning the neural underpinnings of these mechanisms, and whether neural circuitry within the visual cortex might play a causal role in their instantiation, a possibility that we directly tested here. In two related experiments, transcranial magnetic stimulation (TMS) was applied over the lateral occipital cortex of healthy humans at different times during the execution of a behavioral task which entailed varying levels of distractor interference and need for attentional engagement. While earlier TMS boosted target selection, stimulation within a restricted time epoch close to (and in the course of) stimulus presentation engendered selective enhancement of distractor suppression, by affecting the ongoing, reactive instantiation of attentional filtering mechanisms required by specific task conditions. The results attest to a causal role of mid-tier ventral visual areas in distractor filtering and offer insights into the mechanisms through which TMS may have affected ongoing neural activity in the stimulated tissue.